The horse and his boy - Lewis, C. S. (Clive Staples), 1898-1963.; Baynes, Pauline (New York : HarperTrophy, 1994)
A boy and a talking horse share an adventurous and dangerous journey to Narnia to warn of invading barbarians.
Kirkus Review.
Kirkus Review, November 2010.
5.3
5-8
Keywords: Narnia (Imaginary place) -- Juvenile fiction; Fantasy; Narnia (Imaginary place) -- Fiction; Narnia (Imaginary place) -- Fiction; Fantastic fiction; Fantastic fiction